Investigation of calcium carbonate synthesized by steamed ammonia liquid waste without use of additives. Issue 13 (2nd March 2020) - Luo, Xianping; Song, Xuewen; Cao, Yuwei; Song, Lei; Bu, Xianzhong
Abstract : The aim of this work is to study the effect of reaction conditions using steamed ammonia liquid waste without the use of additives on the crystallization of calcium carbonate. Abstract : The aim of this work is to study the effect of reaction conditions using steamed ammonia liquid waste without the use of additives on the crystallization of calcium carbonate. CaCO3 was prepared by steamed ammonia liquid waste (CaCl2 ) and (NH4 )2 CO3 solution. The produced crystals were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectrometry (FTIR) and X-ray diffraction (XRD). We have investigated the effect of the concentration of reactants, stirring speed, Ca 2+ : CO3 2− ratio, aging time and adding mode on the particle size and size distribution, final morphology and polymorph of calcium carbonate crystals during precipitation. The influence of concentration of reactants, stirring speed, Ca 2+ : CO3 2− ratio, aging time and adding mode on the morphology, size and polymorph of CaCO3 particles and possible formation mechanism were discussed. The exploration provides the possibility for large-scale synthesis of CaCO3 materials with controllable morphology and crystallographic structure by steamed ammonia liquid waste without use of additives at room temperature.